What change? Assessing the Extinction Rebellion’s support for climate assemblies - Falanga, R.; Carvalho, T. (Environmental Science and Policy, 2025)
Extinction Rebellion (XR), founded in 2018, advocates for citizens' assemblies (CAs) on the climate and ecological crisis. This demand underscores XR's aim to enhance democracy “beyond politics” and promote inclusive, effective decision-making to achieve change. The article explores XR's understanding of politics and the democratic legitimacy of CAs in driving change. It examines XR's discourse and repertoire of action by triangulating document analysis, consultation of media resources and interviews with some activists in the United Kingdom, Italy, and Portugal. By situating this research within the broader context of global environmental activism and emerging connections with democratic innovations, this article discusses an emerging paradox inherent in XR's support for CAs. XR simultaneously critiques electoral politics and supports CAs, which maintain a strong connection to party politics though. Moreover, while invoking social pressure beyond the realm of CAs, questions arise about what democratic legitimacy the movement attributes to this type of deliberative mini-publics in the pursuit of change.